2006
DOI: 10.1007/s10549-006-9175-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of ATP-binding cassette (ABC) transporters as a predictor of the pathologic response to neoadjuvant chemotherapy in breast cancer patients

Abstract: Drug resistance is a major obstacle to the successful chemotherapy. Several ATP-binding cassette (ABC) transporters including ABCB1, ABCC1 and ABCG2 have been known to be important mediators of chemoresistance. Using oligonucleotide microarrays (HG-U133 Plus 2.0; Affymetrix), we analyzed the ABC transporter gene expression profiles in breast cancer patients who underwent sequential weekly paclitaxel/FEC (5-fluorouracil, epirubicin and cyclophosphamide) neoadjuvant chemotherapy. We compared the ABC transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 32 publications
(39 reference statements)
7
93
1
1
Order By: Relevance
“…These signatures comprise known signatures such as the genomic grade index as well as several new classifiers [25][26][27][28][29][30][31][32][33][34][35][36][37]. Additional data to support the predictive potential for the 70-gene assay comes from the neoadjuvant study of Straver et al [38].…”
Section: Discussionmentioning
confidence: 99%
“…These signatures comprise known signatures such as the genomic grade index as well as several new classifiers [25][26][27][28][29][30][31][32][33][34][35][36][37]. Additional data to support the predictive potential for the 70-gene assay comes from the neoadjuvant study of Straver et al [38].…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies was performed using Affymetrix HG-U133 Plus 2.0 GeneChip which contains all 49 human ABC transporter genes (Table 2). ABC transporter expression profiles were generated using this array from breast cancer patients who received neoadjuvant chemotherapy including 5-FU and paclitaxel [25]. Comparison between patients who had complete response and those who had residual disease revealed that the expression of ABCA1, ABCA12, ABCB6, ABCC5, ABCC11, ABCC13 was elevated in the residual disease group, suggesting that their expression may contribute to the incomplete response of these patients to neoadjuvant therapy.…”
Section: Identification Of Abc Transporter Genes In Drug-selected Celmentioning
confidence: 99%
“…Gillet et al also performed an analysis of 16 breast cancer samples using their low density DualChip human ABC microarray (see below) and found 23 ABC transporters including ABCC1 and ABCC5 were expressed in the majority (≥10 of 16) of the breast cancer samples tested [28]. Unlike the study by Park et al [25], however, the Gillet study [28] did not have the correlation analysis between patient response to chemotherapy and their ABC transporter expression level. Thus, the implication of ABC transporter expression in this study is limited.…”
Section: Identification Of Abc Transporter Genes In Drug-selected Celmentioning
confidence: 99%
“…1,2 However the development of drug resistance is a formidable barrier to successful treatment and correlated with a poor clinical prognosis for the patient. [3][4][5] Furthermore once the breast cancer has metastasized, it is more difficult to effectively treat. Cell motility and multidrug resistance can be governed by extracellular signals from growth factors, 6,7 however the mechanisms responsible for these processes are still not fully known.…”
Section: Introductionmentioning
confidence: 99%